From modern-day parasitology to paleoparasitology: the elusive past record and evolution of Cryptosporidium - Roche, Kévin; Dalle, Frédéric; Capelli, Nicolas; Borne, Romain; Jouffroy-Bapicot, Isabelle; Valot, Benoit; Grenouillet, Frédéric; Le Bailly, Matthieu (Frontiers in Microbiology, 2023)
Recent efforts have been made to review the state of the art on a variety of questions and targets in paleoparasitology, including protozoan taxa. Meanwhile, these efforts seemed to let aside Cryptosporidium, and we then intended to review its paleoparasitological record to assess its past distribution and favored detection methods, and eventually highlight needed research trajectories. This review shows that contrary to other parasites, most of the positive results came from South-American sites and coprolites rather than sediment samples, highlighting the need to test this kind of material, notably in Europe were many negative results were reported in the published literature from sediment samples. Moreover, aDNA-based detections are nearly absent from the paleoparasitological record of this parasite, though punctually shown successful. With their potential to address the evolutionary history of Cryptosporidium species, notably through their 18S rRNA tree, aDNA-based approaches should be encouraged in the future. In sum, and though the limits of currently used methods and materials remain unclear, this review highlights the potential role of coprolites and aDNA for the study of Cryptosporidium species in the past and how this history shaped their current diversity and distribution, notably among human populations but also farm animals.